(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
The Indian banking industry plays an important role in the economic development of the country and is the most dominant segment of the financial sector. It is emerging as one of the fastest vehicle in the panorama of the burgeoning service sector in India. Banking is practically a necessity to business activity and is important for the growth of the economy. It is the center point of the economy as it caters to the need of all sections of the society. Attracting and retaining customers is always a key focus area for banks to be successful. Banks are finding new ways to reach their customers with a mix of traditional and modern techniques. This has necessitated a vigorous distribution system to reach out to customers across the expanse of a vast country especially in India. There is a need of adapting a system with multiple delivery channels which enables banks to expand their pool of potential customers by appealing to a greater number of segments, and catering to a wider range of needs. The present paper focuses on the multiple delivery channels available to bank customers for various banking services and it further examines the role of multiple delivery channels in Banking Industry in India.